x2-6x-41=0

Simple and best practice solution for x2-6x-41=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x2-6x-41=0 equation:



x2-6x-41=0
We add all the numbers together, and all the variables
x^2-6x-41=0
a = 1; b = -6; c = -41;
Δ = b2-4ac
Δ = -62-4·1·(-41)
Δ = 200
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{200}=\sqrt{100*2}=\sqrt{100}*\sqrt{2}=10\sqrt{2}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-6)-10\sqrt{2}}{2*1}=\frac{6-10\sqrt{2}}{2} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-6)+10\sqrt{2}}{2*1}=\frac{6+10\sqrt{2}}{2} $

See similar equations:

| 4x-6-2x/3=4x+6x-3 | | 6m(m)-20=9m | | V(x)=x(8-2x)(5-2x) | | 10y^2-15y-54=0 | | 3(x2-2)=66 | | 3x-5/5-x-3/2=2(x+5) | | 6a=1=3a+10 | | 0.3x-0.25x=-1.375 | | (70y2–3y–54=0) | | 3a+4(a-2)=12-(8-3a) | | 9y+15=820 | | (2x+5)(2x-3)=0 | | 9a+6+2(3a+5)=0 | | 6y-2=8+2y | | X^2+8x16=0 | | 5x-7/3x-8=-6/7 | | 5t-3=-5 | | 4x+20=2x+25 | | 3y+29y=-56 | | 11w=8580w= | | 5x^2=10x=4 | | 5+2(x-5)^4=167 | | 12x+21-9x+21=28x2-175x+15 | | 5x2+2x=0 | | 3x=28x2-175x+15 | | 2/21x+8=x+6 | | s²+4s+30=0 | | 3/4x+2=1/4x−3 | | (s+4)²=-2s | | (x+9)^2=x+11 | | -x^2-7=56 | | 4(x-3)^2=1024 |

Equations solver categories